Deformation mechanism and damage energy evolution of coal body under different gas pressures based on the energy principle - Yongjiang Yu; Xu Dong; Jiaming Liu; Zhiyuan Song; Zhiqiang Wu; Wenjing Guo (Scientific Reports)
Abstract With increasing mining depth, the coal pillars of a coal mine will be in a stressful environment characterized by high gas pressures and unidirectional loading. To investigate the damage evolution characteristics and energy evolution mechanism of coal pillars loaded in a gas pressure environment, a uniaxial compression test was performed on a coal body under different gas pressures using a load testing apparatus for gas-containing coal rocks. The obtained results showed that the mechanical properties of the coal body varied with the gas pressure. Specifically, the peak strain, compressive strength, and elastic modulus decreased with increasing gas pressure; the higher the gas pressure, the lower the conversion rate of the elastic strain energy in the elastic deformation stage of the coal body and the lower its total input energy. With increasing gas pressure, the damage threshold of the coal body decreased, whereas the damage variable corresponding to the peak value, as well as the damage threshold value, increased. According to the theory of continuous damage mechanics, an ontological damage model of the coal body under different gas pressures was established based on the principle of minimum energy dissipation, and the rationality of the model was verified through a comparison between the theoretical and experimental data. Our findings can be useful in ensuring the safety of coal mining in terms of preventing gas disasters.